Optimizing the Village Supervisory Agency's Supervisory Mechanism Through a Participatory and Digital Approach in an Effort to Prevent Criminal Acts of Corruption in Village Development Budgets - Eben Patar Opsunggu; Rineke Sara (Greenation International Journal of Law and Social Sciences, 2025)
Village development budget management is often vulnerable to corruption, primarily due to weak internal oversight systems at the village level. One key oversight actor, the Village Consultative Body (BPD), frequently faces structural constraints, low capacity, and limited authority in optimally carrying out its functions. Yet, the BPD plays a strategic role in ensuring transparency and accountability in the use of village budgets sourced from central government transfers, as specified in Government Regulation No. 37 of 2023. This study analyzes the weaknesses of existing oversight mechanisms and proposes optimization strategies through participatory and digital approaches. With a participatory approach, village communities are encouraged to actively participate in deliberation processes, program evaluations, and budget oversight through community forums and the involvement of vulnerable groups. Furthermore, the use of digital systems such as SISKEUDES, SP4N-LAPOR, and social media-based innovations and QR codes in development projects provides open and real-time data access for the public. This study demonstrates that integrating institutional oversight, community engagement, and digital technology can strengthen village governance and reduce opportunities for budget corruption. Implementing this strategy requires regulatory support, ongoing technical training, and commitment from all stakeholders.